2021
DOI: 10.1093/ofid/ofab022
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural SARS-CoV-2 Testing to Sustain Medically Needed Health Care Delivery During the COVID-19 Pandemic: A Prospective Observational Study

Abstract: Background We implemented a pre-procedural SARS-CoV-2 screening initiative designed to sustain healthcare during a time when the extent of SARS-CoV-2 infection was unknown. Methods Prospective study of patients undergoing procedures at 3 academic hospitals in Pittsburgh, PA (April 21-June 11) and 19 community hospitals across Middle/Western Pennsylvania and Southwestern New York (May 1-June 11). Patients at academic hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Amongst all 130 included studies, 88 studies used more than one method of follow-up to ascertain asymptomatic status (Table 1, S2 Table). Only 22 of 130 studies reported the median or mean age [38,47,70,76,77,83,85,95,99,119-121,124,126,128,133,134,139,143,146,152,164] and only five studies included children only [65,67,110,115,118]. Only 31 studies reported the sex of people with asymptomatic SARS-CoV-2 (Table 1, S2 Table) [38,47,51,53,70,71,75,76,83,85,95,99,107,119-122,124,126,128,133,134,139,143,146,147,150,153,158,162,164].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst all 130 included studies, 88 studies used more than one method of follow-up to ascertain asymptomatic status (Table 1, S2 Table). Only 22 of 130 studies reported the median or mean age [38,47,70,76,77,83,85,95,99,119-121,124,126,128,133,134,139,143,146,152,164] and only five studies included children only [65,67,110,115,118]. Only 31 studies reported the sex of people with asymptomatic SARS-CoV-2 (Table 1, S2 Table) [38,47,51,53,70,71,75,76,83,85,95,99,107,119-122,124,126,128,133,134,139,143,146,147,150,153,158,162,164].…”
Section: Resultsmentioning
confidence: 99%
“…Only 22 of 130 studies reported the median or mean age [38,47,70,76,77,83,85,95,99,119-121,124,126,128,133,134,139,143,146,152,164] and only five studies included children only [65,67,110,115,118]. Only 31 studies reported the sex of people with asymptomatic SARS-CoV-2 (Table 1, S2 Table) [38,47,51,53,70,71,75,76,83,85,95,99,107,119-122,124,126,128,133,134,139,143,146,147,150,153,158,162,164]. The types of included studies changed across the five versions of the review.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, approximately half of patients either declined pre-procedural testing or could not be reached to arrange testing; barriers identified included lack of interest in testing, distance from testing facility, transport issues, and the patient's perception of not being at risk for COVID-19. 99 Positive pre-procedural SARS-CoV-2 testing was associated with delaying of the procedure by 29 days on average, with no COVID-19–related complications identified in any of the patients whether or not their procedure was delayed. 101 Utility of a risk screening questionnaire to identify patients with positive pre-procedural SARS-CoV-2 testing remains unclear; in one study of 1000 patients undergoing endoscopy the negative predictive value of a validated risk screening questionnaire was 99.4%; however, the positive predictive value was only 2.5%.…”
Section: Pre-procedural Testingmentioning
confidence: 86%
“…We found 13 studies that reported on asymptomatic SARS-CoV2 among patients referred for endoscopic procedures who underwent testing. [8][9][10][11][12][13][14][15][16][17][18][19] Across these 13 studies, asymptomatic prevalence ranged from 0.0% to 1.5%, but most studies reported a range from 0% to 0.5% regardless of local surges of COVID-19 cases. A notable example of this is highlighted in 2 UK studies, conducted by the same authors at different time periods and surges; during the first time period from May to June 2020, when local prevalence was low, the asymptomatic prevalence was 0.11% (n ¼ 2611) and during a surge in December 2020, the asymptomatic prevalence remained low (0.37% [9 of 2449]).…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…The panel identified 1 study in which authors reported that 3228 of 5881 patients did not receive preprocedural/presurgical testing; 30.5% were not tested due to inability to reach the patient and the remaining patients (69.5%) declined. 13 The most common reasons for declining were lack of interest in testing (19.2%), distance from testing facility (19.0%), and perception of not being at risk due to self-isolation (9.8%). About 4.1% reported that they did not get tested due to lack of transportation and 1.1% reported fear of going to a testing center.…”
Section: Other Evidence To Decision Considerationsmentioning
confidence: 99%